Heritability and genotype by environment interactions for growth and survival in Litopenaeus vannamei at low and high densities. (22nd January 2016) - Tan, Jian; Luan, Sheng; Luo, Kun; Guan, Jiantao; Li, Wenjia; Sui, Juan; Guo, Zhaojia; Xu, Shengyu; Kong, Jie
Abstract: Genetic parameters and genotype by rearing density interactions for growth traits and survival were investigated in Litopenaeus vannamei . A total of 3626 shrimps from 40 families in two densities (low density, 80 shrimps m −2 ; high density, 160 shrimps m −2 ) were measured for four growth traits, body length, body weight, cephalothorax length and abdominal segment length. Variance components and genetic parameters for growth and survival were estimated using a two‐trait animal model or a threshold (probit) sire and dam model. The common environment effect was excluded because it could not be partitioned effectively, likely because of high heritability. The heritability for growth traits varied from 0.21 to 0.44, indicating a moderate level. For survival, the back‐transformed heritability ( h p 2 ) was 0.36 ± 0.06 and 0.22 ± 0.04 for the low and high densities respectively. There were no significant differences in heritability for growth traits and survival between the two densities ( P  > 0.05). High genetic correlations (0.94–0.98) between the two densities for growth traits indicated a low genotype by density interaction and ranking effect across the environments, which suggested that these traits were controlled mostly by the same genes over the two densities. Therefore, selection in a low‐density environment should produce desired correlated responses for growth at a high density. Genetic correlation (0.77 ± 0.09) between the two densities for survival was moderate and significant, which indicated that the genotype by density interaction effect was moderate and low for survival under the two densities. Our results provide crucial information for use in L. vannamei breeding programmes in China.